The Determinants and Efficiency of Local Authority Spending in England - Gordon, James (IMF Working Papers; Working Paper ;, 1991)
This paper analyzes the efficiency and determinants of local authority expenditure in England during 1989/90. The capitalization of local spending in house prices is used as a test of efficiency, and it is found that local services are in general excessive from this standpoint. The determinants of local government spending are then estimated and local incomes, the tax price faced by the electorate, and local party control are found to be significant. Application of the analysis to the recently introduced local government reforms suggest small effects on the overall level of spending.